2005
DOI: 10.1002/ijc.21584
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal methylation of the common PARK2 and PACRG promoter is associated with downregulation of gene expression in acute lymphoblastic leukemia and chronic myeloid leukemia

Abstract: The PARK2 gene, previously identified as a mutated target in patients with autosomal recessive juvenile parkinsonism (ARJP), has recently been found to be a candidate tumor suppressor gene in ovarian, breast, lung and hepatocellular carcinoma that maps to the third common fragile site (CFS) FRA6E. PARK2 is linked to a novel described PACRG gene by a bidirectional promoter containing a defined CpG island in its common promoter region. We have studied the role of promoter hypermethylation in the regulation of PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 29 publications
3
66
0
Order By: Relevance
“…The absence of correlation between FRA6E break and Parkin expression suggests that other mechanisms are responsible for abnormal expression of Parkin. Abnormal methylation may be one of these mechanisms (Agirre et al, 2005). We hypothesized that the consequences of the PARK2 break on the clinical outcome may be due to a subsequent effect on a 6q gene, telomeric of PARK2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of correlation between FRA6E break and Parkin expression suggests that other mechanisms are responsible for abnormal expression of Parkin. Abnormal methylation may be one of these mechanisms (Agirre et al, 2005). We hypothesized that the consequences of the PARK2 break on the clinical outcome may be due to a subsequent effect on a 6q gene, telomeric of PARK2.…”
Section: Discussionmentioning
confidence: 99%
“…The 6q26-qter region contains several genes including PARK2, FOP, TTLL2, AF-6/MLLT4, KIF25, THBS2 and TBP, potentially involved in cancer (Prasad et al, 1993;Taki et al, 1996;Whitcomb et al, 2003;Denison et al, 2003a;Guasch et al, 2004;Agirre et al, 2005). Among these genes, AF-6/MLLT4, located telomeric of PARK2, encodes the Afadin protein, which is crucial for epithelial physiology and development (Ikeda et al, 1999;Zhadanov et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, epigenetic downregulation of parkin by biallelic hypermethylation of the parkin promoter has been associated with cases of acute lymphoblastic leukemia and chronic myeloid leukemia in blast crisis. (63) However, the contribution of other epigenetically modified genes or aneuploidies in these neoplasms is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reduced expression and inactivation of Parkin are frequently observed in human cancers [8][9][10][11]. It is also reported that Parkin expression can be epigenetically regulated; its expression can be reduced due to abnormal DNA methylation [12]. These studies suggest that Parkin may play a tumour suppressor role.…”
Section: Introductionmentioning
confidence: 91%